2021
DOI: 10.1371/journal.pone.0250696
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to utilize nutrition interventions among lactating women in rural communities of Tigray, northern Ethiopia: An exploratory study

Abstract: Background While lactation is a physiological process requiring high energy demand to fulfill the nutrient requirements of the mother and the breastfeeding child, many factors affecting maternal nutrient intake can lead to nutritional deficits. Previous studies in Ethiopia have reported the prevalence of maternal and child undernutrition and related complications. However, qualitative studies exploring potential barriers to utilizing available nutrition interventions are limited. This study, therefore, sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…This finding revealed that the odds of optimal nutrition and health practices among pregnant women who traveled 30-60 minutes and greater than 60 minutes to get care from health institution were less likely as compared to pregnant women who travel less than 30 minutes. This finding is consistent with the study done in Tigray, Ethiopia, that mothers reported the unavailability of health facilities close to their locality was a key barrier to utilizing available services from health institution [43]. This has an implication that pregnant women are forced to either travel long distances to get health services or otherwise don't access the service given at health institution including nutrition and/or health related issues.…”
Section: Discussionsupporting
confidence: 89%
“…This finding revealed that the odds of optimal nutrition and health practices among pregnant women who traveled 30-60 minutes and greater than 60 minutes to get care from health institution were less likely as compared to pregnant women who travel less than 30 minutes. This finding is consistent with the study done in Tigray, Ethiopia, that mothers reported the unavailability of health facilities close to their locality was a key barrier to utilizing available services from health institution [43]. This has an implication that pregnant women are forced to either travel long distances to get health services or otherwise don't access the service given at health institution including nutrition and/or health related issues.…”
Section: Discussionsupporting
confidence: 89%
“…Poor hygiene and repeated infections also play an important role in the mother's micronutrient status (Henjum et al, 2015 ). Moreover, poor nutrition knowledge, cultural taboos, and gender inequity in the intrahousehold food distribution aggravate poor nutrient intake and maternal malnutrition (Beyene et al, 2021 ). A study recently showed that factors such as age, marital status, educational level, and monthly household income affected the overall diet quality of reproductive‐age women of rural Bangladesh (Akter et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even in high-income countries, low- and middle-income families could not ensure nutritious foods for pregnant women 15 16. A study in Ethiopia stated that the poor economic status of the family was the leading barrier to provide healthy food consumption 17. Another study in Ethiopia showed that around 40% of the pregnant women had low dietary diversity 18.…”
Section: Discussionmentioning
confidence: 99%